2007
DOI: 10.1203/pdr.0b013e3180db29fe
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hemodynamics in Neonatal Lambs Resuscitated with 21%, 50%, and 100% Oxygen

Abstract: ABSTRACT:The effect of resuscitation with varying levels of O 2 on pulmonary hemodynamics at birth is not well known. We hypothesized that the decrease in pulmonary vascular resistance (PVR) and subsequent response to pulmonary vasoconstrictors and vasodilators will differ following resuscitation with 21%, 50%, or 100%O 2 for 30 min at birth in normal term lambs. Lambs at 141 d gestation were delivered by cesarean section and ventilated with 21% (21% Res; n ϭ 6), 50% (50% Res; n ϭ 6), or 100% O 2 (100% Res; n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 32 publications
4
73
0
Order By: Relevance
“…We have also shown that ventilation with 21% O 2 results in a rapid reduction in pulmonary vascular resistance and does not interfere with subsequent vasodilation to NO and acetylcholine, whereas resuscitation with 100% O 2 impairs vasodilation to these agents (8). Because oxidative stress influences apoptosis and cell growth (9), oxygen exposure may have long-term consequences on growth and development.…”
mentioning
confidence: 70%
“…We have also shown that ventilation with 21% O 2 results in a rapid reduction in pulmonary vascular resistance and does not interfere with subsequent vasodilation to NO and acetylcholine, whereas resuscitation with 100% O 2 impairs vasodilation to these agents (8). Because oxidative stress influences apoptosis and cell growth (9), oxygen exposure may have long-term consequences on growth and development.…”
mentioning
confidence: 70%
“…14,15 There is evidence in newborn animal models of asphyxia that exposure to high concentrations of oxygen at resuscitation does not confer any clinical advantage and is potentially harmful at the cellular level. 16,17 Two animal models of hypoxia-ischemia and persistent bradycardia found that those resuscitated with room air rather than 100% oxygen developed untoward biochemical changes in the brain (LOE 5 18,19 ).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…O 2 toxicity and/or chronic ventilation, the two main causes contributing to lung injury in premature infants, may impede K v channel expression/ function in the pulmonary vasculature. More recently, the deleterious effect of even brief (30 min) hyperoxia (decreased vasodilation to nitric oxide and acetylcholine) on the pulmonary circulation was reported (39,40). Interestingly, the authors also show that lambs previously exposed for a brief period (30 min) to 100% O 2 did not have enhanced pulmonary vasoconstriction in response to subsequent hypoxic ventilation.…”
Section: Discussionmentioning
confidence: 92%